UiTM hosts Tokyo university foreign studies students / Dr. Mohd Nadzri Mohd Najib - Mohd Najib, Mohd Nadzri (Faculty of Pharmacy, 2023)
In line with UiTM's strategic goal of establishing itself as a globally renowned university of science, technology, humanities, and entrepreneurship, UiTM Cawangan Pulau Pinang Kampus Bertam recently hosted seven students from Tokyo University Foreign Studies (TUFS) as part of a student-host family program. Led by Dr. Mohd Nadzri Mohd Najib from the Faculty of Pharmacy, the program aimed to foster global connections and cultural understanding between the two universities while promoting UiTM's strategic goals. Seven students from TUFS and one accompanying teacher arrived at Penang International Airport on 21st February at 8:30 pm. They were welcomed by their host family, which consisted of five UiTM staff and two members of the community.